Ticks and Tick-Borne Pathogens 2019
DOI: 10.5772/intechopen.81167
|View full text |Cite
|
Sign up to set email alerts
|

Economic and Health Impact of the Ticks in Production Animals

Abstract: Nowadays there is no doubt about the importance of production animals in the economy and food security of the population throughout the world. For an animal to be productive (cattle, small ruminants, swine or poultry) is needed to be in adequate health conditions. The health of these animals can be altered by the direct and indirect effects of ticks, causing significant losses in the production of meat, milk, eggs, leathers, and in many cases the death of the affected animals. The direct losses are related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 55 publications
2
36
0
Order By: Relevance
“…Other signs include anorexia, yellow mucous membrane, nasal and ocular discharge and reduction in milk yield in lactating animals (Muraleedharan, 2015). About 500 million cattle are at risk throughout the globe (Chaudhry et al, 2010;Oscar and Cristian 2018). Tick borne diseases cause 18.6 billion losses and deficiency of 3 billion pieces of hide in cattle per year (Terkawi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other signs include anorexia, yellow mucous membrane, nasal and ocular discharge and reduction in milk yield in lactating animals (Muraleedharan, 2015). About 500 million cattle are at risk throughout the globe (Chaudhry et al, 2010;Oscar and Cristian 2018). Tick borne diseases cause 18.6 billion losses and deficiency of 3 billion pieces of hide in cattle per year (Terkawi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Tick borne diseases cause 18.6 billion losses and deficiency of 3 billion pieces of hide in cattle per year (Terkawi et al, 2012). Economic losses of production by ticks are about 13-19 billion per year globally (De Castro and Newson, 1993;Oscar and Cristian, 2018). Diminazine aceturate and imidocorb dipropionate are used in the treatment of Babesiosis (Mosqueda et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These results agree with the findings of Remington et al (1997) who found that the increasing weight gain were obtained from treated animals against ticks. Whereas previously infested animals do not grow significantly faster than animal kept tick-free (Seebeck et al 1971;Hurtado et al, 2018). There was a difference in the response of recovering of the lost weight within intervals times, but in the end, there were no significant differences in weight gain for all acaricides treatments, which is associated with the evanescence of acaricidal effects and tick infestation.…”
Section: Discussionmentioning
confidence: 79%
“…Although CCHFV infection control may not have perceived animal health benefits, several approaches can reduce virus exposure in animals (and, in turn, humans) and have positive outcomes beyond CCHFV risk reduction. Decreasing the tick burden on animals by physically removing ticks (see Section 4.1 ) and using acaricides (see Section 6.2 ) can improve the overall health status of an animal or herd and increase production levels [ 110 , 111 ]. These are significant concerns to herd health, so efforts are made to target breeding programs for tick resistance [ 112 ].…”
Section: Risk Reduction: Animal-targeted Approachesmentioning
confidence: 99%